A high-resolution remotely sensed benthic habitat map of the Qatari coastal zone. (November 2020) - Butler, Josh D.; Purkis, Sam J.; Yousif, Ruqaiya; Al-Shaikh, Ismail; Warren, Christopher
Abstract: A comprehensive, high resolution, ground truthed benthic habitat map has been completed for Qatar's coastal zone and Halul Island. The objectives of this research were to; 1. Systematically compare and contrast pixel- and object-based classifiers for benthic mapping in a limited focus area and then to, 2. Apply these learnings to develop an accurate high resolution benthic habitat map for the entirety of the Qatari coastal zone. Results indicate object-based methods proved more efficient and accurate when compared to pixel based classifiers. The developed country-wide map covers 4500 km 2 and underscores the complex interplay of seagrass, macroalgal, and reefal habitats, as well as areas of expansive mangrove forests and microbial mats. The map developed here is a first of its kind in the region. Many potential applications exist for the datasets collected to provide fundamental information that can be used for ecosystem-based management decision making. Graphical abstract: Unlabelled Image Highlights: Acquired hi-resolution, atmospheric/water corrected satellite imagery of coastal zone Habitat map trained and validated with ground truthed data Compared accuracy/efficiency of pixel- and object-based habitat mapping Object based work-flow presented the best results and was applied to the coastal zone. A meter resolution, habitat map with 26 classes was completed for all of Qatar's coast.